The effects of aerobic exercise on biochemical parameters in individuals with CKD on hemodialysis: A longitudinal study - de Oliveira, Fabiano Santana; de Deus Morais, Mauro José; de Abreu, Luiz Carlos; Pérez-Riera, Andrés Ricardo; Valenti, Vitor E [UNESP]; da Silva Paiva, Laércio; Raimundo, Rodrigo Daminello (Faculdade de Filosofia e Ciências, 2020)
Backgroung: Chronic kidney disease is directly related to cardiovascular disorders. Guided physical exercises significantly improve the adverse effects of dialytic treatment. Objective: To analyze changes in biochemical parameters of subjects with chronic kidney disease undergoing moderate exercise during hemodialysis. Methods: This is an experimental study composed of 54 subjects submitted to hemodialysis, split into a control group and a group with intervention. The experimental group underwent three weekly sessions of aerobic exercise, performed during hemodialysis sessions, with a duration of 30 minutes, for 12 weeks. The blood parameters of both groups were compared. Results: Statistically significant differences were observed between pre (p=0.001) and post-exercise protocol for urea (p=0.006), calcium (p=0.001), alanine aminotransferase (p=0.020) and sodium (p=<0.001). In the control group, we observed significant differences for the calcium variable (p<0.001), alanine aminotransferase (p=0.024), hematocrit (p=0.015), calcium vs phosphorus (p=0.018), and sodium (p=0.023), before and after the period. Conclusion: Aerobic training during hemodialysis was able to maintain blood level stability in patients with chronic kidney disease, both during and at the end of the protocol, even considering increased blood flow. This trial is registered in the Brazilian registry of clinical Trials-number RBR-7354r6. Registration date: July 5, 2018 at 12:59 PM. Last Update: July 24, 2018 at 10:24 AM. Identification of the test-UTN Number: U1111-1216-8272.
Keywords: Aerobic exercises; Blood parameters; Chronic kidney disease; Hemodialysis